2004
DOI: 10.1002/jso.20059
|View full text |Cite
|
Sign up to set email alerts
|

Positive margins following surgical resection of breast carcinoma: Analysis of pathologic correlates

Abstract: These data suggest certain pathologic factors that may portend difficulty in achieving negative resection margins in patients in whom breast conservation therapy is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
32
6
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 37 publications
12
32
6
2
Order By: Relevance
“…[7][8][9][10][11]16,17 As far as we know, this is the first study to reveal that BPE is a significant independent factor associated with positive resection margin.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…[7][8][9][10][11]16,17 As far as we know, this is the first study to reveal that BPE is a significant independent factor associated with positive resection margin.…”
Section: Discussionmentioning
confidence: 72%
“…Instead, HER2 tended to be associated with positive resection margin (p 5 0.08). One retrospective study by Miller et al 16 suggested increased risk of positive resection margin associated with HER2 positivity. Similarly, Atalay and Irkkan 30 reported increased risk of having residual disease on re-excision specimen with initial positive margin associated with HER2 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular (stellate) margins did not associate with PgR expression. An association between the tumour margin status and Her-2, ER, or PgR expression has been investigated in several studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Putti et al [29] recently demonstrated that breast tumours with a pushing margin (another terminology for irregular or stellate margin) were found to be ER negative and over expressing Her-2.…”
Section: Discussionmentioning
confidence: 99%
“…While a lumpectomy has clear advantages over mastectomy, one disadvantage is the need sometimes to return to the operating room for a re-excision lumpectomy. Re-excision rates are high, ranging from 20% to 70% in the literature, and in addition to the inconvenience and added costs, re-excision lumpectomies may result in added complications and diminish the aesthetic outcome [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%